Research on optimization of train routing problem for railway hubs considering passenger demand - Yidong Wang (PLoS ONE, 2026)
The railway hub with multiple stations has been more common with the expansion of the railway network. It is imperative to investigate the utilization of multiple stations to meet the travel demand of urban residents. This paper focuses on railway hubs and abstracts the division of labor among multiple stations as an optimization of train routing problem. A mixed integer linear programming model is constructed to minimize the total cost of trains and passengers, with the number of stops, capacity of railway lines and station tracks, and passenger demand of traffic zones considered as constraints. A case study based on a multi-station railway hub is implemented to evaluate the effectiveness of the optimization model. Compared with the other two scenarios, the total cost of the optimization results is reduced by 0.1% and 2.7%. Meanwhile, the proposed optimization scheme also achieves a more balanced and efficient utilization of railway line and station track capacity. Furthermore, the research also proposes several operationally feasible recommendations for railway department to support making division of labor scheme for railway hubs.